Opening up the Library: Transforming our Policies, Practices and Structures - Ball, Joanna; Stone, Graham; Thompson, Sarah (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Momentum is building in the transition to open access for monographs, with a number of funders developing policies and mandates in recent years. The article argues that while libraries play an instrumental role in driving a transition to open science within their institutions this is not reflected in libraries’ approaches to collection development, which are still predicated on purchased content. Libraries are keen to demonstrate that their purchased content is relevant to users, often promoting ‘expensive’ purchased collections over open content. Rather than relegating open to a less-visible second place, the article calls for libraries to acquire and promote open content alongside, and where appropriate with higher priority, than paid-for content. In order to facilitate a transition to open access for monographs, cultural change and leadership is required within libraries to reimagine themselves around open content as the norm, with policies, practices and structures that communicate, enable and promote this shift. The article calls for a collaborative international approach.